Expression and significance of serum vitamin D and LL-37 levels in infants with bacterial pneumonia - Zhao, Shaojie; He, Yixiu; Pan, Menglan; Chen, Bingzhang; Zhang, Siqi; Zhang, Yufeng; Zhu, Yafei (Frontiers in Pediatrics, 2022)
Objective: To investigate the significance of vitamin D and human antimicrobial peptide LL-37 in the occurrence and development of bacterial pneumonia in infants. Methods: From January 2021 to January 2022, 80 infants with bacterial pneumonia were selected, including 33 cases of gram-positive bacterial infection (GP) and 47 cases of gram-negative bacterial infection (GN). During the same period, 40 infants who underwent health examination in our hospital served as the healthy control group. On the day of admission, peripheral blood was collected from pneumonia patients, and during physical examination of controls; and serum LL-37 levels were measured by enzyme-linked immunosorbent assay (ELISA) and serum 25-hydroxyvitamin D [25-(OH)D] levels were measured by electrochemiluminescence. The differences in serum LL-37 and 25-(OH)D levels and their correlation with disease severity were compared. Pearson correlation was used to analyze the correlation between serum 25-(OH)D and LL-37 levels in infants with bacterial pneumonia.Results: The levels of 25-(OH)D and 25-(OH)D deficiency were significantly lower in patients than in controls (all P < 0.05), and the levels of serum LL-37 were significantly higher in pneumonia patients than in controls (P < 0.05).There was no significant difference in serum 25-(OH)D and LL-37 levels between cases with GP and GN (all P > 0.05). The serum 25-(OH)D level was lower in the severe pneumonia group than in the mild pneumonia group and controls, and the 25-(OH)D deficiency rate was higher; the difference was statistically significant (all P < 0.05). The LL-37 level in the severe pneumonia group was lower than that in the mild pneumonia group but higher than that in the control group, and the difference was statistically significant (P < 0.05). The 25-(OH)D level was positively correlated with the LL-37 level (r = 0.781, P < 0.05).Conclusion: A low level of vitamin D is present in infants with bacterial pneumonia, and its status affects the severity and outcome of pneumonia. The level of LL-37 is increased in infants with bacterial pneumonia, but it shows a downward trend with progression of the disease.